PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI SUDUT PUSAT DAN SUDUT KELILING LINGKARAN - Shofia Hidayah; Raifatul Maghfiroh; Izzatul Munawwaroh (LPPM Institut Ahmad Dahlan Probolinggo, 2026)
This study aims to student’s mathematics learning outcomes on the topic of Central angle and circumferential angle of a Circle through the implementation of the Think Pair Share (TPS) learning model. The research method used was Classroom Action Research (CAR) conducted in two cycles. The subjects of this study were 25 students from class XI IPA R 3 MANJ. Data were collected through learning achievement tests, obcervations, and documentation. The results showed a significant improvement in student’s learning outcomes from cycle II. In cycle I, the average student score was 39.6 with a mastery percentage of 61.76% (16 out of 25 student reached the minimum passing grade of 70). After applying the Think Pair Share model in cycle II, the average score increased to 92.8 with a mastery percentage of 88.24% (22 out of 25 student reached the passing grade). Thus, there was an improvement in learning mastery of 26.48%. These findings indicate that the Think Pair Share learning model effectively improves students’ mathematics achievement by encouraging active paerticipation through thinking individually, discussing in pairs, and sharing ideas in class.